Animal models for inducing inflammatory bowel diseases: integrative review - Melo, Nadja Maria da Costa (2021)
Objective: To identify and describe comparatively the chemical models of the induction of inflammatory bowel diseases (IBD) in rodents most used and that best mimic the pathogenesis in humans. Methods: Based on an integrative review in the MEDLINE and LILACS databases, it was investigated which experimental induction models were most cited in articles published from 2004 to 2020, with the descriptors "Colitis/CI", "Colitis model ulcerative" and "Intestinal inflammation model." All empirical articles that addressed one or more inflammation models in rats or mice were included. Results: 239 articles were identified; of these, only ten empirical articles were selected. The most used models were colitis induced by TNBS acid, DSS, and colitis induced by acetic acid (AA). Conclusion: It was possible to identify the most used models to promote the induction of intestinal inflammation in rats, and both models proved to be effective according to the limitations observed in the models described, suggesting the need for new works that use more well-defined protocols and that more fully represent the pathophysiological complexity of the disease.